The investor in ESG mutual funds - Silva, Paulo Pereira da (2021)
The past decade has witnessed a mounting interest in socially responsible mutual funds. In fact, socially responsible investment (SRI) has become quite popular, attracting increasing investment flows and moving from a niche market to a mainstream investment strategy. According to a survey by The Forum for Sustainable and Responsible Investment, the assets under management of SRI mutual funds increased by 1,000% between 1994 and 2013. Recent growth has also been relevant: between 2016 and 2018, the value of investments managed by professional asset managers increased 34%, with sustainable investment accounting for more than 50% of total professionally managed assets in Canada, Australia and New Zealand in early 2018, almost half in Europe, 26% in the United States and 18% in Japan (GSI, 2019)